The role of the guarantee industry in strengthening MSMEs in indonesia during pandemic Covid 19 - Resista Vikaliana; Antoni Ludfi Arifin; Wahyuddin Latunreng; Abdul Bari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Credit guarantees carried out by banks with the Credit Guarantee Agency in this case are the Indonesian Credit Guarantee Corporation (PT Jamkrindo) and PT (Persero) Indonesian Credit Insurance (PT Askrindo) such as a guarantee mechanism so that if there is a transfer of bad credit risk.  This study aims to identify the role of guarantor institutions in strengthening MSMEs in Indonesia during the COVID-19 Pandemic. This study uses qualitative methods, and the data analysis technique used is content analysis. the study of content with reference to the meaning, context, and intent contained in the message. Results Based on the research, it appears that credit guarantees for MSMEs from guarantee institutions encourage the effectiveness of credit guarantees. The role of guarantee institutions for MSMEs in credit guarantees can be more effective if the institutions carry out the development of business partners and implement the integration or digitization of IT systems. During the pandemic, Jamkrindo contributed to the Working Capital Credit Guarantee (KMK) program in the National Economic Recovery (PEN) and mentoring MSMEs.